A Low-cost Approach to Low-power Gas Sensors Based on Self-Heating Effects in Large Arrays of Nanostructures. (2015) - Monereo, O.; Casals, O.; Prades, J.D.; Cirera, A.
Abstract: The usual operation of a conductometric sensor device requires of an external energy source (i.e. an embedded heater). In the last years, the Joule effect in the sensing material, the so called self-heating effect, offered and alternative method to provide this energy: the probing current (or voltage) applied to measure the sensor signal also serves to heat up the sensor active film. Here, evidences of self-heating effects occurring on large arrays of nanostructures fabricated with low-cost methods are provided. The methodology is proven to be suitable to sense gases (humidity, NH3 and NO2) with low-powered heater-free devices.